Novel diagnostic criteria for atrial cardiomyopathy in patients with type 2 diabetes and atrial fibrillation - E. A. Polyanskaya; A. S. Veklich; N. A. Koziolova (Российский кардиологический журнал, 2021)
Aim. To determine additional diagnostic criteria for atrial cardiomyopathy in patients with type 2 diabetes (T2D) and paroxysmal/persistent atrial fibrillation (AF).Material and methods. This cross-sectional screening clinical study included 80 patients with AF and T2D, who were divided into 2 groups depending on the left (LAVI) or right atrial volume index (RAVI) according to echocardiography: the first group included 49 patients with increased LAVI, while the second — 31 patients without changes in LAVI and RAVI. Inclusion criteria were presence of paroxysmal or persistent AF, T2D, age up to 65 years. There were following exclusion criteria: current smoking and less than 1 year old, the presence of cardiovascular and pulmonary diseases, heart failure, implanted artificial pacemaker, prior radiofrequency ablation; valvular heart disease and prosthetics; acute myocarditis, infective endocarditis, hypertrophic, dilated, and restrictive cardiomyopathies, storage diseases, severe liver diseases; thyroid disorders; cancer; acute inflammatory and infectious diseases; alcohol abuse, dementia and mental illness.Results. The groups did not differ significantly in terms of sex, age, cardiovascular risk factors, risk of stroke and bleeding when using anticoagulants, clinical and laboratory parameters, and the structure of drug therapy. The following parameters significant differ between the groups: LAVI (according to study design), mid-regional pro-atrial natriuretic peptide (MR-proANP), glomerular filtration rate (GFR) calculated by creatinine, tissue inhibitor of matrix metalloproteinases 1 (TIMP-1). For MR-proANP, GFR, TIMP-1, ROC curves were created in order to determine its clinical significance and operational characteristics of parameters. GFR, as a diagnostic criterion, showed unsatisfactory clinical significance when constructing the ROC curve: AUC (area under the curve) was 0,38. The MR-proANP of 62,3-85 pmol/L and TIMP-1 of 156 ng/ml and higher allows verification of atrial cardiomyopathy in patients with T2D and AF at AUC of 0,83 (95% confidence interval (CI), 0,73; 0,92) and 0,90 (95% CI, 0,83; 0,98), respectively.Conclusion. The blood MR-proANP concentration of 62,3-85 pmol/L is diagnostic for atrial cardiomyopathy in patients with T2D and AF with the sensitivity and specificity of 96,8% and 75,5%, respectively, while TIMP-1 values of 156 ng/ml and above had the sensitivity and specificity of 90,3% and 87,8%, respectively.